Translating into success : cutting-edge strategies for going multilingual in a global age - Sprung, Robert C. (Robert Charles); Jaroniec, Simone (American Translators Association scholarly monograph series, 2000)
The boom in international trade has brought with it an increased demand for addressing local consumers in their native language and cultural idiom. Given the complex nature and new media involved in communicating with their constituent markets, companies are developing ever more complex tools and techniques for managing foreign-language communication. This book presents select case studies that illustrate the state-of-the-art of language management. It covers a cross-section of sectors, each of which has particular subtleties in language management: software localization fina.